INVESTMENT POTENTIAL OF UKRAINE AFTER THE WAR IN THE CONTEXT OF EUROPEAN INTEGRATION (INNOVATIVE ECONOMY, 2025)
Myhal O.F., Dudarev O.O., Protsiak A.I, Shevchuk Yu.V.  INVESTMENT POTENTIAL OF UKRAINE AFTER THE WAR IN THE CONTEXT OF EUROPEAN INTEGRATIONPurpose. The aim of the article is to study the peculiarities of formation of Ukraine's investment attractiveness in the context of post-war recovery, taking into account new security challenges, European integration processes and the role of strategic communications – in particular, advertising campaigns – as a tool to stimulate the inflow of foreign investment into the national economy. Methodology of research. The following research methods were used to accomplish the tasks set out in the article: a systematic and comprehensive approach – to consider the investment attractiveness of Ukraine as a multifactorial phenomenon formed under the influence of economic, security, information and institutional factors; statistical methods – to assess the volume of foreign direct investment, the sectoral and regional structure of investment, as well as the dynamics of development of the domestic advertising market; tabular method – for a structured presentation of the results of a comparative analysis of national and international advertising campaigns; graphical method – for visualizing key trends, in particular in the form of diagrams and charts. Data processing and graphic design were carried out using modern computer and information technologies.Findings. The current state of Ukraine’s investment attractiveness in the context of military challenges and prospects for post-war recovery is analysed. The dynamics of foreign direct investment inflows is assessed, and the industries that demonstrate the greatest resistance to crisis influences and retain high investment potential even in conditions of high risks are identified. It has been found that strategic communications, in particular targeted advertising campaigns, play an increasingly important role in shaping the positive investment image of the state in the international arena.Originality. This study provides a comprehensive analysis of the formation of Ukraine's investment potential under martial law and post-war recovery, taking into account the latest security challenges, European integration processes, and the impact of strategic communications. Particular attention is paid to the role of advertising campaigns as a modern tool of public diplomacy that can increase confidence in the Ukrainian investment environment. Practical value. The practical significance of the study lies in the formation of applied recommendations for strengthening Ukraine's investment attractiveness in the post-war period through the application of a number of measures and the use of communication tools, including advertising campaigns. The results of the study can be used by public authorities, economic diplomacy institutions and investment agencies to improve approaches to promoting Ukraine as a safe, open and promising destination for foreign direct investment. Key words: investment potential, investment attractiveness, European integration, advertising services market, Ukraine, high value-added goods.
Keywords: investment potential; investment attractiveness; European integration; advertising services market; Ukraine; high value-added goods